Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s13730-020-00482-w
|View full text |Cite
|
Sign up to set email alerts
|

A case report of progressive multifocal leukoencephalopathy during steroid treatment for ANCA-associated renal vasculitis

Abstract: Case report: an 80-year-old woman presented with rapidly progressive glomerulonephritis and was admitted to our hospital. Myeloperoxidase-specific antineutrophil cytoplasmic antibody (MPO-ANCA) was positive. We diagnosed ANCA-associated renal vasculitis (ANCA-RV). Treatment was initiated with intravenous methylprednisolone pulse therapy, followed by prednisolone (PSL) at 30 mg/day. We gradually reduced the PSL dose to 7.5 mg/day over 6 months. At that time, the patient developed disturbances of consciousness w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Regardless, a history of pre-existing disease such as lymphoma causes diagnostic confusion regarding the recurrence of primary disease versus PML, a rare condition. Regardless, a high clinical suspicion and low diagnostic threshold for PML are keys to early diagnosis [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, a history of pre-existing disease such as lymphoma causes diagnostic confusion regarding the recurrence of primary disease versus PML, a rare condition. Regardless, a high clinical suspicion and low diagnostic threshold for PML are keys to early diagnosis [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our case report highlights the importance of screening for PML in autoimmune individuals receiving immunosuppressive therapy, who present with signs and symptoms of a stroke with confusion, even if the initial cranial imaging findings are normal. A review of the literature showed additional case reports, which highlight the potential association of PML in individuals with autoimmune diseases and immunosuppression, including an 80-year-old woman with antineutrophil cytoplasmic antibodies (ANCA)associated renal vasculitis and a 27-year-old with systemic lupus erythematosus (SLE)-rheumatoid arthritis overlap syndrome [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PML has been associated with chemotherapy-induced lymphocytopenia in solid tumors and it has been recorded in a case with follicular lymphoma treated with anti-CD20 monoclonal antibodies, and another spontaneous report was on a patient undergoing treatment for advanced ductal breast carcinoma and systemic sclerosis who developed the disease, whereas it has been discussed that atypical findings should not exclude diagnosis in cases that are not likely to have classical PML [49][50][51][52]. PML has been documented in people with various autoimmune-supposed conditions-apart from MS-who follow immunomodulation therapy, like Systemic Lupus Erythematosus (SLE) in parallel with cancer complications or not, Rheumatoid Arthritis (RA), ANCA-associated vasculitis, autoimmune hepatitis, myositis, ulcerative colitis, lupus nephritis, ankylosing spondylitis and Crohn's disease [53][54][55][56][57][58][59][60][61][62]. Also, PML has possibly been evident in a case with Coronavirus Disease 2019 (COVID-19) as well as in a patient with Hepatitis B virus-induced CD4 lymphocytopenia, while the disease may occur in the context of systemic sarcoidosis without immunosuppression in which it can even be the first sign, and it can initially be mistaken for neurosarcoidosis or other complications of sarcoidosis [63][64][65].…”
Section: Epidemiology Of Jcpyv and Pmlmentioning
confidence: 99%